The Expositions of Expressionism in Elliot Flower’s Winner’s Loss - Wijayanto, Bagus Pratama; Oktavia, Dian; Ayu, Evangelin Rambu; Putri, Alvina Salshabilla Linjani; Pasopati, Rommel Utungga (Educalitra: English Education, Linguistics, and Literature Journal, 2025)
This paper underlines the idea of expressionism in flash fiction of Elliot Flower entitled Winner’s Loss. Expressionism exposes matters of distorted people and object, emotional pain and anguish, unrealistic feelings of modern world, and symbolistic understanding. This story tells about someone who entrusts the money to the main character name Jack and he accidentally loses the money and accuses someone else of being thief. It turns out the money is taken by Jack’s wife because he lies to his wife by saying he did not have the money. By using qualitative method and explorative approach, the analysis includes how any gambling is actually expression of the desperate men. Those who hold to such gambling then are already at loss from the beginning. The money being gambled belongs to anyone but the ones that use it for another useful matter. In conclusion, expressionism in Flower’s flash fiction indicates how the gambling, the loss of money, and the wife’s attitude may intertwine consecutively to show any changing in the story of anyone’s life in general.